Cultural Heritage Management in the Context of Sustainable Tourism: The Case of Öşkvank Monastery (Uzundere, Erzurum) - Ozgeris, Mustafa; Demircan, Neslihan; Karahan, Ayse; Gokce, Oguz; Karahan, Faris; Sezen, Isik; Kulekci, Elif Akpinar (Mdpi, 2024)
This research was carried out at the & Ouml;& scedil;kvank Monastery, located within the Uzundere district of Erzurum province in the northeast of Turkey. & Ouml;& scedil;kvank Monastery is a significant cultural heritage and tourism asset for the region with a history dating back to the 10th century. Despite its importance as a tourism attraction, the monastery currently lacks any protection or management strategy that threatens the transfer of the monastery to future generations. This research focuses on the management of cultural heritage through sustainable tourism development, and it was conducted using a mixed methodology, combining quantitative and qualitative studies. As part of the research, a survey was made, and & Ouml;& scedil;kvank Monastery was evaluated in terms of sustainable tourism principles. The survey results showed that the participants did not appreciate & Ouml;& scedil;kvank Monastery regarding sustainable tourism principles. A SWOT analysis was performed through a focus group study to identify the internal (strengths, weaknesses) and external (opportunities, threats) conditions of the region in relation to sustainable tourism. Based on the SWOT analysis, a TOWS matrix was developed and strategies for sustainable tourism development were formulated. TOWS strategies were classified by the content analysis method, and an eight-step Cultural Heritage Management Framework (CHMF) was prepared.
Keywords: cultural heritage management; sustainable tourism; swot analysis; tows matrix; & Ouml;& scedil;kvank monastery; Uzundere; T & uuml;rkiye